When no single power held hegemony: Thomas Bowrey’s account of Bay of Bengal (1669-1679) - Deliana, Nia; Ozay, Mehmet (AHRC NWCDTP, 2026)
In the bustling maritime world of the seventeenth century Bay of Bengal, commerce thrived as a form of economic cosmopolitanism, a phenomenon where the boundaries of race and religion seemed to dissolve, where Hindu ‘gentiles’, ‘Muslim ‘moors’, Coromandel’s Chuleas (Chuliah), Hadhrami Arabs from Southern Arabia, Bugis from Sulawesi, Buddhist Siamers and diverse Europeans collaborated and competed with a fluidity that transcended sectarian loyalty. These were the unique economic, social and political interactions, decentralised, yet multipolar, that Thomas Bowrey meticulously documented during his nineteen years in the East. His account reveals a world where no single power held hegemony, and where merchant networks functioned as autonomous poles of influence within a complex system of non-Western polities and burgeoning European interest.